Sleep Quality and Blood Glucose Levels in Patients with Type 2 Diabetes Mellitus - Takdir; Sunarsih; Supodo, Timbul (Bantayang Omni Cendekia, 2024)
Background: Diabetes mellitus is a metabolic disorder characterized by the body's inability to use glucose, fat, and protein due to insulin deficiency or insulin resistance, which results in increased blood glucose. Diabetes mellitus attacks all groups of people in the world and should be addressed in order to reduce the prevalence of type 2 diabetes mellitus. Sleep quality is a person's satisfaction with sleep so that a person does not show feelings of fatigue, easily aroused and restless, lethargy and apathy, blackness around the eyes, swollen eyelids, red conjunctiva, sore eyes, fragmented attention, headaches, and frequent yawning or drowsiness. Objective: This study aimed to determine the relationship between sleep quality and blood glucose levels in patients with type 2 diabetes mellitus at Kendari City Hospital. Methods: This study was a quantitative study with a cross-sectional design. The sample was 68 respondents. This study employed purposive sampling. Results: The Fisher's Exact Test showed a p-value of 0.000. This means that there was a relationship between sleep quality and blood glucose levels in type 2 DM patients. To determine the magnitude of the relationship between variables that have chi-square, a phi coefficient (φ) test was carried out with a result of φ 0.627, which means that the relationship between sleep quality and blood glucose levels in type 2 diabetes mellitus patients was statistically significant. Conclusion: Sleep quality significantly affects blood glucose levels in patients with type 2 diabetes mellitus.